Perancangan Sistem Akuntansi Penjualan Tunai Pada Toko Barasaki Siteba - Aisya Gayatri; Afridian Wirahadi Ahmad; Ermatati Hatta (Politeknik Negeri Padang, 2023)
The purpose of this study was to design a cash sales accounting information system used by Barasaki Stores. This research is in the form of observation and interviews. Data was collected by collecting data from Barasaki Stores directly by observing, videotaping all activities, documents and accounting records used, internal control system mechanisms, and functions involved in cash sales at Barasaki Stores, as well as conducting debriefings with store managers and employees which is related. Data were analyzed using descriptive data analysis techniques that compared theoretical knowledge related to the problem to be studied. The results of the analysis show that the cash sales accounting system is not in accordance with the theory, concurrent positions often occur in stores, there is no warehouse function and accounting function, and there are no records and documents related to the cash sales accounting system, and there is no printed serial invoice number on cash sales invoices